BS O09 Enhanced recovery and fast track surgery is applicable with good outcomes in patients undergoing bariatric surgery. (7th December 2022) - Ahmad, Adil; Mahmood, Fahad; Massey, Daniel; Fagbemi, Ona-Omovefe; Nanthakumar, Nakulan; Sokhal, Balamrit; Salgaonkar, Hrishikesh; Sharples, Alistair; Marimuthu, Kanagaraj; Balaji, Nagammapudur; Rao, Vittal
Abstract: Background: Fast track surgery is well established in major centres undertaking bariatric surgery Methods: All patients who underwent bariatric surgery in a high volume centre were included. Patient outcomes in terms of complication rates, length of stay, one day discharge rate and 30 day readmission rate were analysed. Results: 1009 patients (105 gastric band removal, 756 gastric bypass, 104 sleeve gastrectomy and 44 revision surgery) were included in the study. Demographics include: Age 46(20–77), M:F = 190–819; BMI – 44.3 (20.6–62); Wt. – 120.3 Kg (57.4–190.7). Median length of stay was 1.7 (1–23) with 79% 1 day discharge. 19 patients had complications (1.8%) with no mortality. Logistic regression analysis revealed that presence of co-morbidities (OR = 1.92; 95% CI: 1.26–2.94; p=0.002) and history of previous abdominal surgery (OR = 2.22; 95% CI: 1.27–3.89; p = 0.005) increases risk of delayed discharge. The 30 day readmission rate was significantly higher in patients who had concomitant surgery in addition to primary bariatric surgery (Chi squared test p=0.032) and patients who failed the fast track protocol (p-0.000; chi squared = 13.2) Conclusions: Increased understanding of factors which can be optimised may result in even better outcomes in fast track bariatric surgery.